Audiovisual Translation and Multimodality: What Future? - Yves Gambier (Media and Intercultural Communication: A Multidisciplinary Journal)
The future is always difficult to predict, but certain elements can help us anticipate what tomorrow could look like. Today, in different societies, multimodality thanks to digital technology is becoming a dominant format of communication. Therefore, the traditional Western concept of translation is challenged while technology creates new needs and expectations and opens up space for new practices. In fact, because of this rapid technological development (i.e., the digitalization of tools), certain concepts used in Translation Studies (TS) must be revisited: I will refer here in particular to text, sense, authorship, translation unit, and quality (and the variety of evaluation criteria in audiovisual translation/AVT).  AVT, with its complex system of signs, is a relevant example in this new media landscape: its map shows a dynamic research field. It will also be questioned to a certain extent while the borders of TS are moving with the borders of a significant number of other disciplines.